Relationship between Clean, Healthy Living Behaviour, and COVID-19 Infection at the Parigi Public Health Center, West Java, Indonesia - Wa Indhillah, Putri Asyri; Raksanagara, Ardini Saptaningsih; Gondodiputro, Sharon (Althea Medical Journal, 2023)
Background: Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). One form of prevention is implementing Clean and Healthy Living Behaviour (Perilaku Hidup Bersih dan Sehat, PHBS) at the household level. This study aimed to analyze the association between PHBS at the household level and COVID-19 cases at the Parigi Public Health Center, West Java, Indonesia.Methods: This was an unmatched case control study carried out in September–October 2021 with respondents from Parigi Public Health Center, Pangandaran Regency, involving 63 people for each case and control group. Sampling was conducted by the non-probability method. Data were collected using a checklist to measure the implementation of PHBS at the household level. Data were analyzed by statistical analysis, using the Chi-square or Fisher Exact test and Odds Ratio.Results: There was no statistically significant difference between the implementation of PHBS at the household level and the incidence of COVID-19 (p=0.668).Conclusions: The implementation of PHBS at the household level is not related to the incidence of COVID-19. Further studies are needed with  larger population, looking for causal relationship, and controlling for confounding variables.